A study on molecular mechanisms of adiposis induced by long-term treatment of high-fat and high-sucrose in C57BL/6J mice - Li, X; Tu, P; Umar, M; Liu, Q; Luo, W; Yang, X; Zhu, J; Kong, D; Li, M (Physiological research, 2019)
Adiposis is reputed as a twin disease of type 2 diabetes and greatly harmful to human health. In order to understand the molecular mechanisms of adiposis, the changes of physiological, pathological, epigenetic and correlative gene expression were investigated during the adiposis development of C57BL/6J mice induced by long time (9 months) high-fat and high-sucrose diet (HFSD) sustainably. The results showed that mRNA transcription level of the Leptin, Glut4 and Glut2 genes have been obviously changed, which exhibit a negative correlation with methylation on their promoter DNA. The results also revealed that HFSD induced higher level of DNA methyltransferase 1 (DNMT1) in fat tissue might play important role in regulating the changes of methylation pattern on Glut4 and Leptin genes, and which might be one of the molecular mechanisms for the adiposis development.
Keywords: Liver; Animals; konzumní sacharóza; Glucose Transporter Type 4; játra; Diet, High-Fat; Leptin; Time Factors; časové faktory; DNA-(cytosin-5)-methyltransferasa 1; Adiposity; Mice; adipozita; Dietary Sucrose; myši; leptin; Male; DNA (Cytosine-5-)-Methyltransferase 1; přenašeč glukosy typ 4; zvířata; tuková tkáň; mužské pohlaví; Mice, Inbred C57BL; dieta s vysokým obsahem tuků; myši inbrední C57BL; Adipose Tissue